Cyclotides Suppress Human T-Lymphocyte Proliferation by an Interleukin 2-Dependent Mechanism - Gründemann, Carsten; Thell, Kathrin; Lengen, Karin; Garcia-Käufer, Manuel; Huang, Yen-Hua; Huber, Roman; Craik, David J.; Schabbauer, Gernot; Gruber, Christian W. (PLOS ONE, 2013)
Cyclotides are a diverse and abundant group of ribosomally synthesized plant peptides containing a unique cyclic cystine-knotted topology that confers them with remarkable stability. Kalata B1, a representative member of this family of mini-proteins, has been found to inhibit the proliferation of human peripheral blood mononuclear cells. Analysis of T-cell proliferation upon treatment with chemically synthesized kalata B1 mutants revealed a region comprising inter-cysteine loops 1 and 2 of the cyclotide framework to be important for biological activity. Cytokine signaling analysis using an ‘active’ kalata B1 mutant [T20K], and the reference drug cyclosporin A (CsA) demonstrated that treatment of activated T-lymphocytes with these compounds decreased the expression of the interleukin-2 (IL-2) surface receptor as well as IL-2 cytokine secretion and IL-2 gene expression, whereas the ‘inactive’ kalata B1 mutant [V10K] did not cause any effects. The anti-proliferative activity of [T20K] kalata B1 was antagonized by addition of exogenous IL-2. Furthermore, treatment with [T20K] kalata B1 led to an initial reduction of the effector function, as indicated by the reduced IFN-γ and TNF-α production, but the levels of both cytokines stabilized over time and returned to their normal levels. On the other hand, the degranulation activity remained reduced. This indicated that cyclotides interfere with T-cell polyfunctionality and arrest the proliferation of immune-competent cells through inhibiting IL-2 biology at more than one site. The results open new avenues to utilize native and synthetically-optimized cyclotides for applications in immune-related disorders and as immunosuppressant peptides.